Biogas production from mediterranean crop silages - Carvalho, L. (2012)
Anaerobic digestion has proven to be an efficient way for the production of a renewable fuel. The aim of this work was to study the potential use of two crop silages, yellow lupine (Lupinus luteus L.) and oilseed radish (Raphanus sativus var. oleifera cv. Pegletta), for the production of biogas through the process of anaerobic digestion. The use of yellow lupine was due to its capacity for nitrogen fixation, reducing the fertilization needs for the succeeding crop cycle and reducing also the GHG emissions due to the fertilizer production and its field application. The utilization of the oilseed radish was due to its root exudates with nematicide effect, reducing the needs for soil disinfection, working as a biological weapon and also due to the effect on soil compaction of its large roots, working as a bio-driller. The yellow lupine gave rise to 400 m3 of CH4.t-1 VS and the oilseed radish silage produced approximately 300 m3 of CH4.t-1 VS, proving to be good anaerobic substrates. The inoculum used for the batch digesters was sludge from an anaerobic digester of a WWTP.